y dx-4(x+y6)dy=0
Solution
Writing DE in the form P(x,y)dx + Q(x,y)dy = 0 we’ll get P(x,y) = y, Q(x,y) = -4(x+y6)
∂P/∂y=1 ≠ ∂Q/∂x=-4
Let’s find function M(x,y), called an integrating factor, for which equality ∂(M(x,y)P(x,y))/∂y=∂(M(x,y)Q(x,y))/∂x is satisfied.
-[∂P/∂y - ∂Q/∂x]/P=-5/y
So M(x,y) may be found from equation
dM/M = -[∂P/∂y - ∂Q/∂x]dy/P=-5dy/y
ln|M| = -5ln|y|+lnC
M = C/y5
Multiplying DE by M(x,y) with arbitrary constant C=1
dx/y4-4(x/y5+y)dy = 0
Let’s find function u(x,y) for which du = uxdx+uydy = 0, where ux = 1/y4 and uy = -4(x/y5+y)
u(x,y) = ∫dx/y4 + f(y) = x/y4 + f(y) , where f(y) – arbitrary function.
uy = -4 x/y5 +f’(y) = -4(x/y5+y) => f’(y) = -4y => f(y) = -2y2 - C
Substituting this into expression for u(x,y) we’ll get
u(x,y) = x/y4 - 2y2 - C
Therefore general solution of DE is x/y4 - 2y2 = C
Comments
Leave a comment